Reconstruction of sediment transfers from the Irish Sea margin and the Fleuve Manche (English Channel) palaeoriver over the last climatic cycles - Toucanne, Samuel (HAL CCSD, 2008)
The Pleistocene has been period of fluctuating climate accompanied by prominent sea-level lowstands during the glacial intervals, when massive continental ice sheets extended from mountainous to lowland European areas. The retreat of the shoreline on the extensive present-day shallow continental shelf of the southern part of the British Isles induced the appearance of the ‘Fleuve Manche' palaeoriver, one of the largest systems that drained the European continent. Sedimentary records from the Bay of Biscay offer an independent record allowing the reconstruction of the freshwater and sediment discharges of the ‘Fleuve Manche', and the possibility of detecting the imprint of surrounding ice-sheet oscillations and attendant modification of hinterland drainage directions throughout the Pleistocene. For the last 1.2 Ma, the progressive development of extensive Pleistocene ice-sheets over Europe during cold periods favoured sedimentary transfers in the Bay of Biscay, particularly since MIS 12 when the British and Fennoscandian ice sheets merged in the North Sea for the first time, forcing the North Sea fluvial system to flow southwards through the Dover Strait, which opened 455 000 years ago according to our data. From this point onwards, the North Sea drainage, as well as meltwaters that flowed westwards along the southern margin of the Fennoscandian ice-sheet could drain into the Bay of Biscay, as reported through significant terrigenous supplies in the northern Bay of Biscay during the MIS 6 (ca.150 ka) and MIS 2 (ca.18 ka). We assume for example that sediment load delivered to the Bay of Biscay by the ‘Fleuve Manche' reached 130 M t yr-1 at time of the last melting of the European ice sheet ca. 18 000 years ago. On the whole, we demonstrate, for the studied period, that climate forcing strongly affects the sediment transfer into the northern Bay of Biscay and the turbiditic activity of the Celtic and Armorican turbidite systems. Finally, the recognition of melting events of the European ice sheets throughout the ...